Usage of stories for elementary learners - Pakirdinova Sh, Nazariyon Shamsiya (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article I will write about story, storytelling, benefits of stories for elementary learners. Should all teachers include stories in their every lesson? Or set it down for leisure time of students? And I will share my own experience of usage of stories in teaching.